Traduccions i usos sintàctics de l'expressió de l'abstracció - Guzman, Josep Roderic (Caplletra. Revista Internacional de Filologia, 2007)
The study of translation norms is a key element in traductological studies. Insofar as these norms are linked to cultures and specific historical periods, the analysis of their diverse elements is of fundamental importance. One of the variables that composes these norms is the model of language of the translations, which is devised from the stylistic uses of the translators, mainly from some aspects of language which are particularly controversial. One of them is the syntactic uses for the expression of abstraction, and this paper focuses on their study. The conclusion is that there areless stylistic resources used and centred in no more than a couple of structures despite the several possibilities existing to express abstraction. Many forms recommended by grammarians appear, at best, with scarce manifestations. The reasons for this lack ofuse are varied, probably because of the same translators some times, but also because of the recipients of the translations, who perceive these forms as unusual and, in other cases, as interferences.